2021
DOI: 10.1002/path.5628
|View full text |Cite
|
Sign up to set email alerts
|

Serial genomic analysis of endometrium supports the existence of histologically indistinct endometrial cancer precursors

Abstract: The endometrium is unique as an accessible anatomic location that can be repeatedly biopsied and where diagnostic biopsies do not extirpate neoplastic lesions. We exploited these features to retrospectively characterize serial genomic alterations along the precancer/cancer continuum in individual women. Cases were selected based on (1) endometrial cancer diagnosis/hysterectomy and (2) preceding serial endometrial biopsies including for some patients an early biopsy before a precancer histologic diagnosis. A co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 64 publications
0
36
0
Order By: Relevance
“…This number is comparable to a recent serial genomic analysis of endometrial cancer progression, where next generation sequencing-directed immunohistochemistry found that 86% of endometrial cancers were aberrant for at least 1 of the 5 non-Pax2 markers, with persistence of AH/EIN marker patterns in samples from each patient. 37 Conversely, since 7.2% of bona fide AH/EIN were not aberrant for any of these markers, lack of aberrancy of all 3 should not dissuade from a diagnosis of AH/EIN when definitive histologic features are present.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This number is comparable to a recent serial genomic analysis of endometrial cancer progression, where next generation sequencing-directed immunohistochemistry found that 86% of endometrial cancers were aberrant for at least 1 of the 5 non-Pax2 markers, with persistence of AH/EIN marker patterns in samples from each patient. 37 Conversely, since 7.2% of bona fide AH/EIN were not aberrant for any of these markers, lack of aberrancy of all 3 should not dissuade from a diagnosis of AH/EIN when definitive histologic features are present.…”
Section: Discussionmentioning
confidence: 98%
“… 14 This likely reflects a sequential acquisition of mutations that characterize clonal outgrowth in early endometrial neoplasia. 19 , 37 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In endometrial hyperplasia, PTEN and KRAS have been reported to have mutations frequently. [8][9][10][11][12][13] In addition, recent studies using next generation sequencer revealed many driver gene mutations in atypical hyperplasia and even in normal endometrial glands. [13][14][15][16] Li et al analyzed formalin-fixed paraffin embedded tissue with a diagnosis of atypical endometrial hyperplasia and found frequent mutations in driver genes, including PTEN, ARID1A, CTNNB1, KRAS, and PIK3CA.…”
Section: Molecular Profile Of Endometrial Lesionsmentioning
confidence: 99%
“…It is important to note that these mutations were confirmed in the invasive cancer. This research provided unique insights into precancer initiation and progression and clearly demonstrated the existence of endometrial premalignant lesions with definitive mutations not readily identifiable by histology [ 100 ]. These findings are also supported by a case report in which tumor-specific mutations were identified in an asymptomatic individual without clinical or pathologic evidence of cancer nearly one year before symptoms developed, i.e., postmenopausal bleeding and a single microscopic focus of EC diagnosed at the time of hysteroscopy [ 101 ].…”
Section: Endometrial Precancerous Lesions and Early-stage Endometrial Cancermentioning
confidence: 99%